Answer:
B. x² - 3x - 40
Explanation:
The factored form of quadratic function:
![y=a(x-x_1)(x-x_2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z392oxxl2mur6p0akgd2rlttou7j0ioawq.png)
where x₁ and x₂ are the roots of the quadratic function and the solutions of the corresponding quadratic equation.
We have x₁ = 8 and x₂ = -5. Substitute:
![y=a(x-8)(x-(-5))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5hqkb131iar6gkbk3qdu3orsusxo2dtuuu.png)
use FOIL: (a + b)(c + d) = ac + ad + bc + bd
![y=a[(x)(x)+(x)(5)+(-8)(x)+(-8)(5)]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vxynujfuox06pxncm4z005312keghindcr.png)
![y=a(x^2+5x-8x-40)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w48coqgduj4h8tsup92wvriefnq18twmko.png)
![y=a(x^2-3x-40)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ixsjfoxrq2amm2e90ja6qpboaqvng7sfn7.png)
For a = 1 we have the equation:
B. x² - 3x - 40